IMPLEMENTASI PROGRAM JAMINAN PERSALINAN (JAMPERSAL) DI KABUPATEN PEMALANG, JAWA TENGAH (TAHUN 2011-2013) - Nur Azizah; Tri Cahyo Utomo; Ahmad Taufiq (Journal of Politic and Government Studies, 2014)
ABSTRACTThis research was conducted to find out about Implementation of Delivery AssuranceProgram (Jampersal) in Kabupaten Pemalang, Central Java. Jampersal is financial assuranceused for prenatal care, delivery assistance, and post-partum care, including family planningservices, postpartum and newborn care. Health is a fundamental service for humans, therefore ina state, health care is preferred, and the handling should be optimized in order to realize theoptimum benefit of society. The maternal mortality rate is quite high in Kabupaten Pemalangwhich: in 2010 the maternal mortality rate amounted to 197 per 100,000 live births which is thehighest maternal mortality in Central Java. Thus, the problem is on How is the effectiveness ofJampersal policy to cope with the high Maternal Mortality Rate (AKI) at the time of delivery inKabupaten Pemalang. What is the constraint factors Jampersal policy in dealing with high levelof maternal mortality rate in Kabupaten Pemalang, Central Java?In order to explain the study the researchers used qualitative research with descriptivetype. This approach descriptive research is intended to collecting information about the status ofexisting symptoms. Qualitative research is to identify the descriptive research characteristics,phenomenon and event structure in their natural context. The data source was obtained fromsecondary sources. The scope of analysis through a qualitative approach addressed to therelevant agencies implementing the delivery assurance program which undertaken by KabupatenPemalang health authorities, health personnel performance and user community feedback on thedelivery assurance benefits.The results showed that when viewed from implementation criteria according to EdwardIII, the results of the implementation of delivery assurance program at Kabupaten Pemalang has beengoing well but, still there are some problems such as security benefits of service deliveryincluding: There are still many people who do not meet the requirements to use the serviceguarantees delivery include: 1) the existence of people who do not have identity cards and familycards thus inhibiting the funding mechanism Jampersal claims made by health workers. 2) Manypeople delivery assurance services recipients do not use family planning program in accordancewith the applicable rules in the program, so it trigger a population explosion. 3) The servicedelivery assurance is still concentrated in hospitals, resulting in a full hospital, thus the hospitalcould not perform the task optimally.The recommendation for this research is the need to increase the socialization of the needfor family planning health services, increase efforts to better health assurance as well as tooptimize the implementation of health services effectively and efficiently and on target.